2020
DOI: 10.1007/s12273-020-0629-y
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based assessment of data center waste heat utilization using aquifer thermal energy storage of a university campus

Abstract: The global energy consumption of data centers (DCs) has experienced exponential growth over the last decade, that is expected to continue in the near future. Reasonable utilization of DC waste heat, which is dissipated during the computational process, can potentially be an effective solution to mitigate the environmental impact. However, the practical implementation of waste heat utilization in the DC environment is a very challenging task. The possible benefits of waste heat utilization are uncertain and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
8
2
Order By: Relevance
“…This field consists of building a model that mimics a real system's behavior based on explicitly defined physical laws and heuristic expressions [77] [81] [17] [49] [14] [21]. If the simulator approaches real-world systems, they provide high-fidelity data.…”
Section: Simulation Based Modelsmentioning
confidence: 99%
“…This field consists of building a model that mimics a real system's behavior based on explicitly defined physical laws and heuristic expressions [77] [81] [17] [49] [14] [21]. If the simulator approaches real-world systems, they provide high-fidelity data.…”
Section: Simulation Based Modelsmentioning
confidence: 99%
“…Academic data centers are typically known to be less efficient. In 2014 Choo et al [10] reported a PUE of 2.73 and in 2020, Dvorak et al [11] reported a PUE of 1.78 for the academic data centers they studied.…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the literature over the last five years, we found eleven case studies on academic data centers; of these, only five (i.e., [11,[37][38][39][40]) analyzed the reuse of waste heat. In all five studies, the waste heat that can be reused from the academic data center was determined using analytical methods with waste heat temperatures that were calculated based on consumer use of the data center rather than measured in real time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal environment optimization can affect the building energy use, while building energy use can also react to the thermal environment changes. Heating, ventilating and air-conditioning (HVAC) system is an important part of contemporary building sectors, which directly and significantly affects both indoor thermal environment and energy use (Dvorak et al, 2020). Building sectors are responsible for 20-40% of the total energy consumption in different countries, of which HVAC systems account for 40-60% (Alimohammadisagvand et al, 2016;.…”
Section: Introductionmentioning
confidence: 99%